Plants neither possess nor require consciousness - Taiz, Lincoln; Alkon, Daniel; Draguhn, Andreas; Murphy, Angus; Blatt, Michael; Hawes, Chris; Thiel, Gerhard; Robinson, David G. (Trends in plant science, 2019)
In claiming that plants have consciousness, ‘plant neurobiologists’ have consistently glossed over the remarkable degree of structural and functional complexity that the brain had to evolve for consciousness to emerge. Here, we outline a new hypothesis proposed by Feinberg and Mallat for the evolution of consciousness in animals. Based on a survey of the brain anatomy, functional complexity, and behaviors of a broad spectrum of animals, criteria were established for the emergence of consciousness. The only animals that satisfied these criteria were the vertebrates (including fish), arthropods (e.g., insects, crabs), and cephalopods (e.g., octopuses, squids). In light of Feinberg and Mallat’s analysis, we consider the likelihood that plants, with their relative organizational simplicity and lack of neurons and brains, have consciousness to be effectively nil.